PENGARUH BEBAN KERJA DAN KESEJAHTERAAN DOSEN TERHADAP KEPUASAN KERJA DAN BURNOUT - Sulistyowati, Arini; Muazansyah, Imam (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
The growing national development, higher education was temporarily changed, following the dynamics of globalization. As an educational institution, higher education has a noble mission, which is to educate and improve the quality of human resources, either through formal education in the framework of knowledge development, or through training (non-formal education) in order to improve skills. This research was conducted with the aim to know the influence of workload and prosperity of lecturer to job satisfaction and burnout. This study uses a quantitative approach. Data collection using primary and secondary data. Data analysis technique used is SEM analysis by using PLS. The results in this paper show that (1) There is no significant influence with the negative direction of Workload on Job Satisfaction; (2) There is no significant influence with the negative direction of Workload on Burnout; (4) There is no significant influence with positive direction of Welfare of Lecturer to Burnout at lecturer at University of Indonesia, (5) There is no significant influence with positive direction of Job Satisfaction on Burnout to lecturers at universities throughout Indonesia. Â Keyword: Workload, Lecturer Welfare, Job Satisfaction, Burnout